Remarking Waves: The Quebec Women's Movement in the 1950s and the 1960s - Gosselin, Cheryl (Canadian Woman Studies / Les Cahiers de la femme, 2006)
Keywords: Femmes

Pratiques et stratégies d'appropriation spatiale des groupes de femmes montréalais - Bêchard, Clotilde (Université du Québec à Montréal, 2008)
Keywords: Femmes

Femmes et sikhisme à Montréal: le cas des représentations des femmes et des rapports homme-femme - Vig, Julie (Université du Québec à Montréal, 2009)
Keywords: Femmes; Indiens

La participation des femmes au processus de migration transnationale familiale: le cas des Shi'ites libanais à Montréal - Le Gall, Josiane (Université de Montréal, 2002)
Keywords: Famille; Femmes; Libanais

Féminisme et mouvement des femmes au Québec. Un bilan complexe - Maillé, Chantal (Globe: revue internationale d’études québécoises, 2000)
Keywords: Femmes; Féminisme

La petite reine et les femmes: la bicyclette au Québec, 1880-1920 - Gagné, Amélie (Université du Québec à Montréal, 2004)
Keywords: Cyclisme; Femmes

Les transformations identitaires de femmes immigrantes indiennes de religion hindoue vivant à Montréal - Ladouceur, Nadya (Université du Québec à Montréal, 2002)
Keywords: Femmes; Indiens

Les femmes et la politique dans les caricatures de Robert La Palme, 1943-1951 - Turgeon, Alexandre (Revue d'histoire de l'Amérique française, 2009)
Keywords: Caricature; Femmes

La légitimité incertaine des travailleuses du sexe dans le mouvement des femmes au Québec - Toupin, Louise (Globe: revue internationale d'études québécoises, 2009)
Keywords: Femmes; Prostitution

Les liens associatifs des femmes chiliennes - Grabowiecka, Marie-Sophia (Université du Québec à Montréal, 2008)
Keywords: Chiliens; Femmes; Féminisme

Québécoises Deboutte!: Le Front de libération des femmes du Québec, le Centre des femmes et le nationalisme - Mills, Sean (Mens, 2004)
Keywords: Femmes; Féminisme; Nationalisme

Des femmes converties à l'islam en France et au Québec: religiosités d'un nouveau genre - Mossière, Géraldine (Université de Montréal, 2009)
Keywords: Femmes; Musulmans

Documentaire interactif Paseo: promenade avec des femmes latino-américaines de Montréal - Rojas Huerta, Ivan (Université du Québec à Montréal, 2004)
Keywords: Femmes; Latino-Américains

Capital social et détresse psychologique: deux réalités connexes: étude de cas des femmes monoparentales haïtiennes de Montréal - Carle, Marie-Ève (Université du Québec à Montréal, 2003)
Keywords: Femmes; Haïtiens

Femmes, ethnicité et religion: la communauté tamoule hindoue du Sri Lanka à Montréal - St-Germain Lefebvre, Catherine (Université du Québec à Montréal, 2008)
Keywords: Femmes; Sri Lankais

Commercialisation des produits de beauté, pratiques esthétiques et représentations du corps de la femme à Montréal, 1870-1915 - Chartrand, Mélanie (Université de Montréal, 2004)
Keywords: Femmes; Publicité

Race, classe, genre: le discours et les pratiques du milieu communautaire vis-à-vis des femmes monoparentales haïtiennes de Montréal - Henry, Irvine (Université de Montréal, 2002)
Keywords: Femmes; Haïtiens

Les femmes et la ville en temps de guerre et en temps de paix. Montréal dans les années 1940 - Fahrni, Magda (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Femmes; Guerre

Corps-fait-histoire dans le processus de mondialisation, de migration et d'insertion: parcours de femmes immigrantes péruviennes à Montréal - Rojas-Viger, Celia (Université de Montréal, 2004)
Keywords: Femmes; Péruviens

Madeleine Parent, une indéfectible alliée des femmes autochtones - Rouleau, Michèle (Madeleine Parent, militante, 2003)
Keywords: Autochtones; Femmes; Parent, Madeleine

Jeunes femmes et loisirs commerciaux durant les années folles (1919-1929): Étude des discours ecclésiastiques et journalistiques - Comtois, Patricia (Université du Québec à Montréal, 2007)
Keywords: Femmes; Patin; Ski

La place des femmes dans la Société d'art contemporain: Montréal, 1939-1948 - Fortin, Nathalie (Université du Québec à Montréal, 2007)
Keywords: Femmes; Société d'art contemporain

Le mouvement des femmes au Canada de 1970 à 2000: définir nos priorités - Kaye, Lynn; McDonald, Lynn (Madeleine Parent, militante, 2003)
Keywords: Femmes; Féminisme; Parent, Madeleine

Femmes et changement social au Québec. L’apport de la jeunesse ouvrière catholique (1931-1966) - Piché, Lucie (Presses de l’Université Laval, 2003)
Keywords: Femmes; Jeunesse ouvrière catholique (JOC)

Mobilité et accessibilité aux services et aux transports des femmes âgées à Montréal - Murat, Chesena (Université de Montréal, 2006)
Keywords: Automobile; Femmes; Transport en commun

La représentation de l'héroïne dans les romans historiques québécois (1945-1995) ayant comme trame de fond la Nouvelle-France. Les femmes en trois actes: l'épouse, la mère et la veuve - Gingras, Marie-Ève (Université de Sherbrooke, 2008)
Keywords: Femmes; Roman

"S'unir pour être plus fort": le Conseil des femmes membres de la Chambre de commerce du district de Montréal, 1956-1971 - Detellier, Élise (Université de Montréal, 2004)
Keywords: Chambre de commerce; Femmes

L'enfermement asilaire des femmes au Québec: 1873-1921 - Thifault, Marie-Claude (Université d'Ottawa, 2003)
Keywords: Femmes; Hôpital Saint-Jean-de-Dieu; Hôpitaux psychiatriques

"Elles sont partout": Les femmes et la ville en temps d'épidémie. Montréal, 1918-1920 - Fahrni, Magda (Revue d'histoire de l'Amérique française, 2004)
Keywords: Bénévolat; Communautés religieuses; Femmes; Infirmières; Épidémies

Des salons aux annales: les réseaux et associations des femmes de lettres à Montréal au tournant du XXe siècle - Savoie, Chantal (Voix et Images, 2002)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste; Journalistes

Pointe Saint-Charles: un quartier, des femmes, une histoire communautaire - Le Collectif CourtePointe [Isabelle Drolet et Anna Kruzynski] (Les éditions du remue-ménage, 2006)
Keywords: Femmes; Groupes populaires; Idéologies; Pointe-Saint-Charles; Quartiers

Mères célibataires et infanticides à Montréal 1914-1930 - Lévesque, Andrée (Femmes et justice pénale: XIXe-XXe siècle, 2002)
Keywords: Enfants; Femmes

Entre la folie d'un seul homme et les violences faites aux femmes: la mémoire collective entourant les événements de la tuerie du 6 décembre 1989 - Blais, Mélissa (Université du Québec à Montréal, 2007)
Keywords: Commémoration; Femmes; Féminisme; École polytechnique

Le Montreal Council of Women / Conseil des Femmes de Montréal, de 1940 à 1967, à travers les questions de planification urbaine, d'immigration et des femmes dans le monde du travail - Hilairet, Sabine (Université d'Angers, 2003)
Keywords: Femmes; Féminisme; Montreal Local Council of Women; Travail

Maternalisme et État-Providence. Le cas du Québec - Baillargeon, Denyse (Sextant (Revue du Groupe interdisciplinaire d'études sur les femmes, 2003)
Keywords: Assistance maternelle; Femmes; Fédération nationale Saint-Jean-Baptiste; Féminisme; Goutte de lait; Montreal Local Council of Women

"Les femmes accélèrent la machine de guerre": le travail des femmes durant la Seconde Guerre mondiale dans Le Monde ouvrier - Detellier, Élise (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2003)
Keywords: Confédération des travailleurs catholiques du Canada (C.T.C.C.); Conseil des métiers et du travail de Montréal; Femmes; Fédération des travailleurs et travailleuses du Québec (FTQ); Guerre

Eleanor Moore Ashton (1917-): la femme et son œuvre montréalaise - De Lorimier, Élaine (Université du Québec à Montréal, 2000)
Keywords: Danse

Comment une militante a conquis le cœur des femmes immigrantes du Québec - Mulay, Shree (Madeleine Parent, militante, 2003)
Keywords: Parent, Madeleine

Femmes de soir (théâtre); suivi de Contours: réflexion à partir du théâtre africain-américain - Amoni, Emmanuelle (Université du Québec à Montréal, 2000)
Keywords: Africains; Noirs; Théâtre

Les représentations de la femme dans l’œuvre scénique de Diane Dufresne, 1975-1984 - Lafrenière, Marilyne (Université du Québec à Trois-Rivières, 2008)
Keywords: Chanson; Musique

Jean Despréz [Laurette Larocque] (1906-1965). Une femme de tête, de courage et de coeur - Simard, François-Xavier; La Rose, André (Les Éditions du Vermillon, 2002)
Keywords: Journalistes; Radio; Radio-Canada; Roman; Théâtre

La vision romanesque de la femme dans L'Invitée de Simone de Beauvoir et dans Bonheur d'occasion de Gabrielle Roy - Wardhaugh, Ana Paula Fernandes (Université du Manitoba, 2005)
Keywords: Roman; Roy, Gabrielle

"Au-delà des apparences: le corps investi par le voile": discours, représentations et pratiques de femmes musulmanes originaires de l'Iran, du Maroc et de la Tunisie ayant immigré à Montréal - Gagné, Isabelle (Université Laval, 2009)
Keywords: Iraniens; Maghrébins; Marocains; Musulmans; Tunisiens

La participation des organismes communautaires montréalais à la sphère municipale: Regard sur les pratiques et les stratégies des organismes qui œuvrent auprès des communautés ethnoculturelles, des femmes et des organismes qui interviennent sur les enjeux urbains - Latendresse, Anne; Messier, Jérôme; Grenier, Geneviève (Département de géographie de l'Université du Québec à Montréal, 2004)

Éva Circé-Côté, journaliste montréalaise au-delà de la singularité - Lévesque, Andrée (Interrelations femmes-médias dans l'Amérique française, 2009)
Keywords: Circé-Côté, Éva; Journalistes

Évolution sociodémographique et demande de logements en milieu urbain: le cas de la région métropolitaine de Montréal, 2001-2021 - Codo, Pamphile (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2006)
Keywords: Femmes

Immigrant Women Entrepreneurs in Montreal: Building Business and Lives - Simpson, Joni (Université Concordia, 2006)
Keywords: Femmes

Female Skateboarders and their Negotiation of Space and Identity - Porter, Natalie Louise (Université Concordia, 2003)
Keywords: Femmes

Perspectives féminines sur les hommes et le couple. Châtelaine, 1960-1975 - Malo, Isabelle (Université de Montréal, 2005)
Keywords: Femmes

Traf: A History of Trafalgar School for Girls - Gillett, Margaret (Trafalgar School for Girls, 2000)
Keywords: Femmes

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens

Working for Pay and Managing the Household - Baillargeon, Denyse (Labouring Canada: Class, Race, and Gender in Canadian History, 2008)
Keywords: Femmes; Travail

Voices of Portuguese Immigrant Women - Januário, Ilda; Marujo, Manuela (The Portuguese in Canada: From the Sea to the City, 2000)
Keywords: Femmes; Portugais

L'histoire des Montréalaises: un chantier en construction - Baillargeon, Denyse (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Femmes; Histoire

Genre, religion et politiques sociales au Québec dans les années 1930. Les pensions aux mères - Cohen, Yolande (Revue canadienne de politique sociale, 2006)
Keywords: Famille; Femmes

A Ritual Transformed: Women Smokers in Montreal, 1888-1950 - Rudy, Jarrett (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: Femmes; Tabac

Shattered Nevra: Performances of Distress and Resistance among Greek Immigrant Women in Montreal - Xenocostas, Spyridoula (Université de Montréal, 2000)
Keywords: Femmes; Grecs

Pratiques et stratégies spatiales des employées de bureau montréalaises dans un contexte de décentralisation économique - Chicoine, Nathalie (Institut national de la recherche scientifique et Université du Québec à Montréal, 2001)
Keywords: Femmes; Travail

Un Québec en mal d’enfants: la médicalisation de la maternité, 1910-1970 - Baillargeon, Denyse (Remue-ménage, 2004)
Keywords: Enfants; Femmes

Montreal Synagogue Sisterhoods (1900-1949): A Female Community, Culture, and Religious World - Goodman, Donna (Université Concordia, 2004)
Keywords: Femmes; Juifs

William Notman’s Portrait Photographs of the Wealthy English-speaking Girls of Montreal: Representations of Informal Female Education in Relation to John Ruskin’s “Of Queens’ Gardens” and Writings by and for Canadians from the 1850s to 1890s - Lerner, Loren Ruth (Revue d'histoire de l'éducation / Historical Studies in Education, 2009)
Keywords: Bourgeoisie; Femmes

La médicalisation de la maternité au Québec comme enjeu de pouvoir (1910-1970) - Baillargeon, Denyse (Pouvoir médical et santé totalitaire: conséquences socio-anthropologiques et éthiques, 2009)
Keywords: Femmes; Médecine

Mode, société et apparence: la mode féminine au Québec de 1945 à 2000 - Dulac, Françoise (Université Laval, 2003)
Keywords: Femmes; Vêtements

La médicalisation de la maternité au Québec, 1910-1970: autour de la notion de risque - Baillargeon, Denyse (Une démographie au féminin: risques et opportunités dans le parcours de vie / A Female Demography: Risks and Chances in the Life Course, 2009)
Keywords: Femmes; Médecine

Women’s Workplaces: The Impact of Technological Change on Working-Class Women in the Home and in the Workplace in Nineteenth Century Montreal - Bradbury, Bettina (Rethinking Canada. The Promise of Women’s History, 2002)
Keywords: Femmes; Travail

A Home away from Home: Defining, Regulating, and Challenging Femininity at the Julia Drummond Residence in Montreal, 1920–1971 - Kirkland, Elizabeth (Urban History Review / Revue d'histoire urbaine, 2006)
Keywords: Femmes; Logement

Statut d'immigration, agentivité et référents identitaires: l'expérience migratoire d'immigrantes maghrébines - Morin, Marie-Pier (Université de Montréal, 2009)
Keywords: Femmes; Maghrébins

Your Roots Will Be Here, Away from your Home: Migration of Greek Women to Montreal 1950-1980 - Dounia, Margarita (Université McGill, 2004)
Keywords: Femmes; Grecs

Agents of Change, Colours of Resistance: The Socio-Economic Integration of Filipina Live-In Caregivers in Montreal - Kapiga, Isabelle (Université Concordia, 2009)
Keywords: Femmes; Philippins

Sur le front intérieur. Les ménagères québécoises de la seconde guerre mondiale: rationnement et récupération - St-Onge, Mélissa (Université de Montréal, 2007)
Keywords: Femmes; Guerre

The Feminization of Clerical Work in Early Twentieth-Century Montreal - Boyer, Laura Kate (Université McGill, 2001)
Keywords: Femmes; Travail

Identité ethnique et identité érotique: le cas de lesbiennes d'origine haïtienne - Ambrosi, Sophie (Université de Montréal, 2005)
Keywords: Femmes; Haïtiens

Community, Identity, and Religious Leadership as Expressed through the Role of the Rabbi's Wife - Landau-Chark, Susan J. (Université Concordia, 2008)
Keywords: Femmes; Juifs

Italian Immigrant Women and Literacy: A Case Study - Constantino, Patricia (Université Concordia, 2001)
Keywords: Femmes; Italiens

The Conservation of a Gender Fantasy: Women and Top 40 Radio in Montreal - Maki, Christine (Université McGill, 2008)
Keywords: Femmes; Radio

Montreal's Designing Women - s.a. (The Beaver, 2000)
Keywords: Confection; Femmes

Plus que parfaites: un siècle de services domestiques à Montréal - Bourbeau, Amélie (Cap-aux-Diamants, 2001)
Keywords: Domestiques; Femmes

Faith, Family, Female Education and Friendship: Retelling Louise Amelia Monk's Adolescence in Bourgeois Montreal, 1867-1871 - Brettler Vandervort, Jessica L. (Université Concordia, 2003)
Keywords: Bourgeoisie; Femmes

L’immigration féminine au Canada durant les années 1920: la mise en place d’une politique fondée sur le "genre" - Vallée, Marie-Hélène (Recherches féministes, 2002)
Keywords: Britanniques; Femmes

''Don't Let Your Girlfriends Ruin Your Marriage'': Lesbian Imagery in Chatelaine Magazine, 1950-1969 - Korinek, Valerie Joyce (Rethinking Canada History. The Promise of Women's History, 2002)
Keywords: Femmes; Mariage

La migration féminine qualifiée d’origine sud-américaine à Montréal: ressources culturelles et symboliques, et stratégies d’accès au marché de l’emploi - Guillen Castro, Maritza (Université de Montréal, 2009)
Keywords: Femmes; Travail

Roughing It in the Suburbs. Reading Chatelaine Magazine in the Fifties and Sixties - Korinek, Valerie Joyce (Studies in Gender and History, 2000)
Keywords: Femmes; Féminisme

Living Water, Sacred Space: An Outsider's Look at Contemporary Mikveh Practice - Searle, Suzan (Université Concordia, 2008)
Keywords: Femmes; Juifs

Une voix féminine dans l’espace public. La Galerie Dominion, 1941-1956 - Pageot, Édith-Anne (Globe: revue internationale d'études québécoises, 2008)
Keywords: Femmes; Peinture

Structurations particulières du temps et de l’espace chez quatre écrivaines québécoises d’origine est-européenne - Ringuet, Chantal (Globe: revue internationale d'études québécoises, 2003)
Keywords: Femmes; Écrivains

Maternidad y migración: Entre recuerdos y pensares: Historias de vida de quince mujeres latinoamericanas que habitan en Montréal (Canadá) - Bedoya Idrobo, Luz Marina (Université de Montréal, 2009)
Keywords: Femmes; Latino-Américains

Bending the Rules: The Montreal Branch of the Woman's Art Association of Canada, 1894-1900 - Haskins, Victoria (Université Concordia, 2005)
Keywords: Art association; Femmes

Étude de cas. Joséphine Marchand-Dandurand: la lecture au féminin - Montreuil, Sophie (Histoire du livre et de l'imprimé au Canada, vol. II (1840-1918), 2005)
Keywords: Femmes; Marchand-Dandurand, Joséphine

Représentations des immigrantes roumaines sur leurs usages d'internet en contexte d'immigration à Montréal - Regus, Oriane (Université du Québec à Montréal, 2008)
Keywords: Femmes; Internet; Roumains

The Harsh Welcome of an Industrial City: Immigrant Women in Montreal, 1880-1900 - Gauvreau, Danielle; Olson, Sherry; Thorton, Patricia (Histoire sociale / Social History, 2007)
Keywords: Femmes; Mariage; Travail

Visualising the History of Women at Eaton's, 1869 to 1976 - O'Donnell, Lorraine Frances (Université McGill, 2002)
This thesis examines the place of female customers and employees at the T. Eaton Company of Canada between 1869 and 1976. The central argument is that the word "witness" conveys well the nature of their place in this, one of the most important retail firms in Canadian history. Women were witnesses for the Eaton's and its development. They attested to and consolidated the company by collectively supporting it in huge numbers, whether as customers or personnel. Women were also key eyewitnesses of Eaton's, of its merchandise and marketing, its stores and catalogues. As the word "witness" suggests, visuality was central to women's central place. Women bought into the Eaton's buying and selling strategies that privileged appearances, and the company assumed and fostered this visually-centered role, helping to construct it and encouraging women to adopt it. The Introduction to the thesis reviews the substantial literature on the company's history. The main body of the thesis is divided in two. Part I examines the company's foreign activities and the role of women therein. Following a description of the firm's foreign buying system is an examination of three of its main regions: Japan, Europe and the U.S.A. The closer the region was to Canada, the more familiar it was to Eaton's, the more female Eatonians were employed there, and the more these women were able carve out a niche for themselves as expert witnesses like fashion buyers or fashion reporters. Part II discusses the place of women in the company's activities within Canada. First, it outlines the history of and tensions between the company's two main retail sites: stores and catalogues. While run by men, these sites were "spectacles of women" including salesclerks, mannequins and customers. Examples considered in depth are Eaton's catalogue covers and store displays for foreign goods and places. They privileged female imagery, a strategy meant to add value both to the merchandise and the (incomplet)
Keywords: Eaton; Femmes; Magasins

Migrants in Montreal: Managing British Female Immigrants at the Turn of the Twentieth Century - Chilton, Lisa (British Journal of Canadian Studies, 2003)
Keywords: Britanniques; Femmes; Protestants

Culture et conflit intergénérationnel dans la famille cambodgienne à Montréal: les récits des mères - Khai, Sophearath (Université du Québec à Montréal, 2008)
Keywords: Cambodgiens; Famille; Femmes

Indispensable but not a Citizen: the Housewife in the Great Depression - Baillargeon, Denyse (Contesting Canadian Citizenship. Historical Readings, 2002)
Keywords: Crise; Famille; Femmes

"Don't I Long for Montreal": l'identité hybride d'une jeune migrante franco-américaine pendant la Première Guerre mondiale - Fahrni, Magda; Frenette, Yves (Histoire sociale / Social History, 2008)
Keywords: Américains; Femmes; Français

Regulating Public Space in Early Nineteenth-Century Montreal: Vagrancy Laws and Gender in a Colonial Context - Poutanen, Mary Ann (Histoire sociale / Social History, 2002)
Keywords: Droit; Femmes; Itinérance

The Historical Record and Adolescent Girls in Montreal’s Red-Light District - Myers, Tamara (Framing Our Past: Constructing Canadian Women’s History in the Twentieth Century, 2001)
Keywords: Enfants; Femmes; Prostitution

On Probation: The Rise and Fall of Jewish Women's Antidelinquency Work in Interwar Montreal - Myers, Tamara (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: Délinquance; Femmes; Juifs

Itineraries of Marriage and Widowhood in Nineteenth-Century Montreal - Bradbury, Bettina (Mapping the Margins: The Family and Social Discipline in Canada, 1700-1975, 2004)
Keywords: Femmes; Mariage; Veuvage

Indispensable but not a Citizen: the Housewife in the Great Depression - Baillargeon, Denyse (Rethinking Canada: the Promise of Women's History, 2006)
Keywords: Crise; Famille; Femmes

Facteurs déterminants des styles parentaux des mères haïtiennes immigrantes à Montréal - Jean-Baptiste, Larissa (Université de Montréal, 2002)
Keywords: Famille; Femmes; Haïtiens

Vers l’avenir. Québec Women’s Politics Between 1945 and 1967: Feminist, Maternalist and Nationalist Links - Gosselin, Cheryl A. (Université de Montréal, 2002)
Keywords: Femmes; Féminisme; Nationalisme

Class, Gender, and the Social Standard: The Montreal Junior League, 1912–1939 - Chenier, Elise (Canadian Historical Review, 2009)
Keywords: Anglophones; Bourgeoisie; Femmes

Le voyage virtuel. Les consommatrices, le monde de l'étranger et Eaton à Montréal, 1880-1980 - O'Donnell, Lorraine (Revue d'histoire de l'Amérique française, 2005)
Keywords: Eaton; Femmes; Magasins

Les Jeunes Laurentiens. Jeunesse, militantisme et nationalisme dans le Canada français des années 1940 - Rajotte, David (Université de Montréal, 2006)
Keywords: Femmes; Idéologies; Nationalisme

Persister et signer: Les signatures féminines et l’évolution de la reconnaissance sociale de l’écrivaine (1893-1929) - Savoie, Chantal (Voix et Images, 2004)
Keywords: Femmes; Journalistes; Écrivains

One (Wo)man’s Shopping is the Same (Wo)man’s history? Immigration, Advertisement and Consumption Patterns in the Greek community of Montreal 1960s-1970s - Pabst, Stavroula (Études canadiennes / Canadian Studies, 2009)
Keywords: Femmes; Grecs; Publicité

Vive la Canadienne! Les représentations de l’identité féminine dans le défilé de la Saint-Jean-Baptiste à Montréal (1924-1961) - Demers, Michel (Université de Sherbrooke, 2001)
Keywords: Femmes; Saint-Jean-Baptiste (fête)

Une jeunesse unique? Mouvements de jeunesse et contestation sociale - Piché, Lucie (Études d'histoire religieuse, 2001)
Keywords: Femmes; Jeunesse ouvrière catholique (JOC)

Talons hauts et bas de soie: les téléphonistes de Bell Téléphone à Montréal, 1920-1939 - Bouvie, Emmanuelle-Minnie (Université du Québec à Montréal, 2004)
Keywords: Bell Canada; Femmes; Téléphone

Fréquentations et mariage, les représentations de jeunes québécoises à travers l'étude d'un courrier du coeur (1958-1968) - Sénéchal, Johanne (Université Laval, 2006)
Keywords: Bertrand, Janette; Femmes; Mariage

The Women's Movement in Canada: Setting the Agenda - Kaye, Lynn; McDonald, Lynn (Madeleine Parent: Activist, 2005)
Keywords: Femmes; Féminisme; Parent, Madeleine

Madeleine Parent: an Unfailing Ally of Native Women - Rouleau, Michèle (Madeleine Parent: Activist, 2005)
Keywords: Autochtones; Femmes; Parent, Madeleine

Democracy, Dissent, and the City: Cross-Cultural Encounters in Sixties Montreal - Mills, Sean (The Sixties in Canada: a Turbulent and Creative Decade, 2009)
Keywords: Femmes; Féminisme; Noirs; Travail

A Maternalist Organization in Quebec: The Fédération Nationale Saint-Jean-Baptiste and the Struggle for Women’s Suffrage - Hébert, Karine (Quebec since 1800: Selected Readings, 2002)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste

Counting the Costs of Living: Gender, Citizenship, and a Politic of Price in 1940s Montreal - Fahrni, Magda (Canadian Historical Review, 2002)
Keywords: Alimentation; Femmes; Prix; Épicerie

Du silence à l'affirmation: Women Making History in Point St. Charles - Kruzynski, Anna (Université McGill, 2004)
Keywords: Femmes; Pointe-Saint-Charles; Quartiers

Hier ne meurt jamais. Vision et désillusions d'une quête identitaire féminine au Québec. La Bonne Parole, organe de la Fédération nationale Saint-Jean-Baptiste, 1913-1958 - Dornic, Isabelle (Université Laval, 2004)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste

La revue l'Oiseau bleu (1920-1940) de la Société Saint-Jean-Baptiste de Montréal: première jonction entre la littérature de jeunesse et la littérature féminine - Blanchet, Sophia (Université du Québec à Trois-Rivières, 2004)
Keywords: Enfants; Femmes; Société Saint-Jean-Baptiste

Plus que parfaites: les aides familiales à Montréal, 1850-2000 - Groot, Raphaëlle de; Ouellet, Élizabeth (Remue-ménage, 2001)
Keywords: Domestiques; Femmes; Institut du Bon-Conseil

Les services du Traveller’s Aid pour l’accueil aux immigrants: identités de genre et de religion au Québec au XXe siècle - Cohen, Yolande (L'État canadien et la diversité culturelle et religieuse, 1800-1914, 2009)
Keywords: Femmes; Young Women's Christian Association (YWCA)

Travail social et maternité hors mariage au Québec, 1950-1970: entre doctrine catholique et progressisme - Brunet, Marie-Hélène (Université de Montréal, 2006)
Keywords: Communautés religieuses; Femmes; Soeurs de Miséricorde

J’haïs les féministes. Le 6 décembre 1989 et ses suites - Blais, Mélissa (Les éditions du remue-ménage, 2009)
Keywords: Commémoration; Femmes; Féminisme; École polytechnique

Les Gouttes de lait de Montréal. Une institution médicale aux multiples usages - Baillargeon, Denyse (Espaces et temps de la maternité, 2002)
Keywords: Femmes; Goutte de lait; Hôpital Sainte-Justine

Unmaking Manly Smokes: Church, State, Governance, and the First Anti-Smoking Campaigns in Montreal, 1892-1914 - Rudy, Jarrett (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2001)
Keywords: Alcool; Femmes; Prohibition; Tabac; Tempérance

Carabines, poutchinettes co-eds ou freschettes sont-elles des étudiantes? Les filles à l’Université McGill et à l’Université de Montréal (1900-1960) - Hébert, Karine (Revue d'histoire de l'Amérique française, 2004)
Keywords: Femmes; Université McGill; Université de Montréal; Étudiants

Les filles-mères à l'hôpital de la Miséricorde de Montréal 1889-1921 - Eon, Mathilde (Université d'Angers, 2000)
Keywords: Enfants; Femmes; Hôpital de la Miséricorde; Hôpitaux

Changing Times / Les temps changent - K. Paterson, Alex (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; Femmes; Juifs; University Club; Université McGill

The Protestant Orphan Asylum and the Montreal Ladies' Benevolent Society: A Case Study in Protestant Child Charity in Montreal, 1822-1900 - Harvey, Janice (Université McGill, 2001)
Keywords: Enfants; Famille; Femmes; Montreal Ladies' Benevolent Society; Protestants

L’idéal maternel: discours, représentation et célébration des mères québécoises à l’occasion de la fête des mères, 1940-1980 - Marando, Nancy (Université de Montréal, 2006)
Keywords: Enfants; Famille; Femmes; Montreal Star; Presse (La)

Divided by the Ballot Box: The Montreal Council of Women and the 1917 Election - Brookfield, Tarah (Canadian Historical Review, 2008)
Keywords: Femmes; Féminisme; Montreal Local Council of Women; Élections

Une histoire sociale du curling au Québec, de 1807 à 1980 - Richard, Pierre (Université du Québec à Trois-Rivières, 2006)
Keywords: Clubs; Curling; Femmes; Francophones; Montreal Curling Club

La représentation féminine dans le contenu publicitaire de La Presse et Le Devoir pendant la Seconde Guerre mondiale (1939-1945): deux visions opposées - Roy, Stéphanie (Université de Sherbrooke, 2007)
Keywords: Devoir (Le); Femmes; Guerre; Presse (La); Publicité

The Point is... Grassroots Organizing Works: Women from Point St. Charles sharing stories of solidarity - Le Collectif CourtePointe [Isabelle Drolet et Anna Kruzynski] (Les éditions du remue-ménage, 2006)
Keywords: Femmes; Groupes populaires; Idéologies; Pointe-Saint-Charles; Quartiers

Les Midinettes de 1937: culture ouvrière, culture de genre, culture ethnique - Lévesque, Andrée (1937: un tournant culturel, 2009)
Keywords: Confection; Femmes; Syndicats internationaux; Union internationale des ouvriers du vêtement pour dames

Le logement communautaire à Montréal: satisfaction résidentielle et insertion socio-spatiale - Morin, Richard; Bouchard, Marie J.; Frohn, Winnie; Bodson, Paul; Chicoine, Nathalie (Canadian Journal of Urban Research / Revue canadienne de recherche urbaine, 2005)
Cet article porte sur l'apport du logement communautaire A la satisfaction residentielle et a l'insertion socio-spatiale des personnes qui y habitent Les auteurs menent d'abord une reflexion generale sur les cooperatives (COOP) et les organismes sans but lucratif (OSBL) d'habitation comme alternative aux logements du marche et aux logements publics. Puis, ils rendent compte des resultats d'une enquete conduite aupres de locataires sans emploi stable, en particulier des jeunes et des femmes a la tete de familles monoparentales, residant dans des logements COOP et OSBL du quartier Hochelaga-Maisonneuve a Montreal. Cette enquete revele des taux eleves de satisfaction residentielle et une insertion sociale, a des degres divers, de ces locataires dans leur voisinage et leur quartier, mais sans etablir une relation directe entre le logement communautaire et le sentiment d'appartenance au quartier.
Keywords: Logement